RECONSTRUCTING ARABIC LANGUAGE EDUCATION FOR THE REVIVAL OF ISLAMIC CIVILIZATION IN THE DIGITAL AGE - Syaudah, Laely; Susiawati, Iis; Manalu, Samsiah (Universitas Pendidikan Indonesia, 2025)
Arabic has historically served not only as the language of the Qur’an and Islamic sciences but also as a civilizational medium sustaining intellectual and cultural cohesion across the Muslim world. In the digital era, however, Arabic language education faces persistent challenges: grammar-centric curricula, limited relevance to learners’ contexts, and insufficient integration of technology with Islamic values. This conceptual study—grounded in Islamic educational philosophy and critical literature synthesis (2022–2025)—reconstructs Arabic pedagogy through a civilizational lens and proposes the Madrasah of Civilization model. The framework integrates three interdependent dimensions: turāth-based and communicative Arabic proficiency, adab-centered ethical formation, and technology-enhanced global literacy. Findings argue for bridging traditional instruction with digital innovation and moral-spiritual formation via blended learning, value-rich digital platforms, and curriculum redesign that embeds the ontological and epistemological roles of Arabic in Islam. Operational indicators include teacher capacity building in value-based digital pedagogy, cross-institutional collaboration, and assessments that capture linguistic, ethical, and collaborative outcomes. Ultimately, Arabic education should evolve from a discrete subject into a strategic platform for cultivating ethically grounded, globally competent Muslim learners capable of contributing to the renewal of Islamic civilization.